Faktor-faktor yang Mempengaruhi Dinamika Kelompok dan Hubungannya dengan Kelas Kemampuan Kelompok Tani di Desa Pulokencana Kabupaten Serang - Inta PN Damanik (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
Group dynamics is an important factor in the development offarmers' groups. The aims of this study is to know the differences between of farmer group dynamics which includes highest class with lowest class. The results showed that there was no relationship between class ability of farmer groups with the level of group dynamics. Capability class of farmers group evaluation which undertaken in the village Pulokencana only based on an assessment of the head of farmers group and age of group only.The fact that Banjar Tani group is more dynamic than the Banyu Mukti group, but the class between that two groups very different, Banyu Mukti is Main class while the Banjar Tani is Beginners class. Factors that affect the group dynamics are land area, family size, age of group leader and age of farmer groups, and the reception of members of the group leader. In addition, the eight elements of group dynamics, only two elements that do not affect the group dynamics, namely the element of group objective and group pressure. Meanwhile, the six elements that influence group dynamics, the task function has the strongest influence on the dynamics of farmer groups.Keywords: farmer group, group dynamics